Realisasi Kegiatan Program Daerah dalam Pengembangan Pembibitan Sapi Potong Guna Mendukung Swasembada Daging Nasional - Bambang Winarso (Politeknik Negeri Lampung., 2014)
Regional autonomy is given broad authority, real and accountable to local governments in proportion. In line with the local government should be able to utilize the potential of area resources optimally. However, under Regulation No 25 ps 2 verse 3, yr 2000 showed that specific authority perbibitan and arrangements regarding disease prevention remains a central government authority in this regard is Breed Livestock Directorate. Do with the efforts to develop livestock breeding cattle in various respo . In an effort to increase the population of cattle beef cattle , a policy that could be done by the East Java Provincial Government